How to prepare a power system for 12% wind energy penetration: The Portuguese Case Study - Estanqueiro, Ana (2013)
The 2001/77/CE Renewable Energies European Directive together with Kyoto Protocol ratification supported by a Government vision and strong objective on the reduction of external oil dependence put Portugal in the front line to achieve one of the highest wind energy penetrations within ten years time. This paper gives a summarized overview of the Portuguese technical approaches and methodologies followed in order to plan and accomodate the ambitious wind power goals to 2010/2013, preserving the overall quality of the power system.